2016
DOI: 10.1002/bit.26188
|View full text |Cite
|
Sign up to set email alerts
|

FX knockout CHO hosts can express desired ratios of fucosylated or afucosylated antibodies with high titers and comparable product quality

Abstract: During antibody dependent cell cytotoxicity (ADCC) the target cells are killed by monocytes and natural killer cells. ADCC is enhanced when the antibody heavy chain's core N-linked glycan lacks the fucose molecule(s). Several strategies have been utilized to generate fully afucosylated antibodies. A commonly used and efficient approach has been knocking out the FUT8 gene of the Chinese hamster ovary (CHO) host cells, which results in expression of antibody molecules with fully afucosylated glycans. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…genetic engineering of recombinant cell lines (Louie et al, 2016;Yamane-Ohnuki et al, 2004); (b) addition of enzyme inhibitors (Allen et al, 2016;Okeley et al, 2015); (c) modification of the levels of cofactors and substrates involved in glycosylation, including supplementation with alternative sugars (Hossler et al, 2014;Hossler et al, 2017); and (d) fine-tuning of cell culture process parameters (Konno et al, 2012). Of the many cell culture process parameters known to impact glycosylation previously (Hossler, Khattak, & Li, 2009), osmolality was shown to affect afucosylation (Konno et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…genetic engineering of recombinant cell lines (Louie et al, 2016;Yamane-Ohnuki et al, 2004); (b) addition of enzyme inhibitors (Allen et al, 2016;Okeley et al, 2015); (c) modification of the levels of cofactors and substrates involved in glycosylation, including supplementation with alternative sugars (Hossler et al, 2014;Hossler et al, 2017); and (d) fine-tuning of cell culture process parameters (Konno et al, 2012). Of the many cell culture process parameters known to impact glycosylation previously (Hossler, Khattak, & Li, 2009), osmolality was shown to affect afucosylation (Konno et al, 2012).…”
mentioning
confidence: 99%
“…This change in afucosylation can have a considerable impact on the potency of a mAb: a~1% increase in afucosylation can increase ADCC activity by~14-28%(Louie et al, 2016;Thomann et al, 2016). This change in afucosylation can have a considerable impact on the potency of a mAb: a~1% increase in afucosylation can increase ADCC activity by~14-28%(Louie et al, 2016;Thomann et al, 2016).…”
mentioning
confidence: 99%
“…For example, knocking out Fut8 or FX genes can achieve fully afucosylated glycoforms 19 . FX knockout cell line can be supplementated with fucose to express antibodies with desired ratio of fucosylated to afucosylated glycans 20 . Host cells may also be engineered to reduce some host cell proteins susceptible to be retained as impurity during downstream processing which may have an adverse impact on the product during processing or storage 21 .…”
Section: Host Cells and Host Cell Engineeringmentioning
confidence: 99%
“…The work of a number of groups over the years has been directed at the development of afucosylation specific assays [6][7][8][9]. Using controlled mixtures involving homogeneous afucosylated and fucosylated antibodies to control overall afucosylation content, Chung et al [6] first demonstrated the existence of a linear dose-response curve between activity and afucosylation content.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the technical difficulties associated with acquiring the reagents needed to implement afucosylation specific assays at low afucosylation content appear to have been solved by the elegant work of Louie and coworkers. Louie et al [9] used a FX KO CHO cell line and controlled fucose feeding to produce antibodies with different levels of afucosylation. This method allowed them to use a single cell line thus enabling the expression of different levels of afucosylated antibodies without significantly altering the overall glycoform distribution.…”
Section: Introductionmentioning
confidence: 99%